2001
DOI: 10.1523/jneurosci.21-11-04074.2001
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Enhancement of Delayed Hyperalgesia Induced by Repeated Heroin Administration: A Sensitization Process

Abstract: It is difficult to conceive that tolerance and sensitization processes, two apparently opposite phenomena, can concomitantly modify one given biological process, i.e., the processing of pain. We have shown recently that opiates produce not only analgesia but also long-lasting hyperalgesia in rats. This suggests that tolerance to the analgesic effect of an opiate, especially heroin, could be in part the result of an actual sensitization of pronociceptive systems. Here, we show that both magnitude and duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
175
0
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(197 citation statements)
references
References 37 publications
12
175
0
10
Order By: Relevance
“…This is similar to other reports that as few as two low dose injections of heroin or 4 bolus doses of fentanyl can induce mechanical hyperalgesia , Celerier et al, 2000. The duration of hyperalgesia has been reported to lengthen with each exposure to heroin (Celerier et al, 2001). This may at least partly explain the prolonged mechanical allodynia in young rats following cessation of IM.…”
Section: Withdrawal-associated Mechanical Allodyniasupporting
confidence: 90%
See 1 more Smart Citation
“…This is similar to other reports that as few as two low dose injections of heroin or 4 bolus doses of fentanyl can induce mechanical hyperalgesia , Celerier et al, 2000. The duration of hyperalgesia has been reported to lengthen with each exposure to heroin (Celerier et al, 2001). This may at least partly explain the prolonged mechanical allodynia in young rats following cessation of IM.…”
Section: Withdrawal-associated Mechanical Allodyniasupporting
confidence: 90%
“…This study did not differentiate whether the prolonged allodynia is a result of 1) a delay in the maturation of paw withdrawal thresholds or 2) the presence of prolonged withdrawalassociated allodynia. Hypersensitivity long into the abstinent period has been previously reported in adult rats following heroin or fentanyl (Laulin et al, 1998, Celerier et al, 2000, Celerier et al, 2001. At the neural level, prolonged excitation persist long after abstinence in dorsal root ganglion cultures exposed to chronic morphine (Crain and Shen, 1995).…”
Section: Withdrawal-associated Mechanical Allodyniamentioning
confidence: 77%
“…This induction of hyperalgesia by chronic opiate treatment is a timedependent process (Celerier et al, 2001;Li et al, 2001). Our present results showed that chronic morphine did not produce a significant difference in nociceptive response measurements between the morphine-treated rats and the normal saline rats (Figure 3a and b).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat model for such experiments, this pain vulnerability developed after the exposure to high doses of opioids could be revealed by naloxone administration, whereas NT did eventually normalize. 13,32 In the present study, sevoflurane demonstrated potentially beneficial properties that could decrease naloxone-induced hyperalgesia.…”
Section: Discussionmentioning
confidence: 59%
“…6,12,19,31 Further evidence of this phenomenon originates from experimental studies that report hyperalgesia lasting for several days after heroin or fentanyl administration. 32,33 The concept of general balanced anesthesia is defined by the co-administration of several pharmacological agents, so as to enhance their beneficial effects while reducing the side effects of individual drugs administered in high doses. 34 Clinical studies have reported that the reduction of intraoperative opioid doses is associated with diminished postoperative pain and reduced morphine consumption.…”
Section: Discussionmentioning
confidence: 99%